Four Tier-Magnetic Diagnostic Test (4T-MDT): Instrumen Evaluasi Medan Magnet Untuk Mengidentifikasi Miskonsepsi Siswa - Irnin Agustina Dwi Astuti; Yoga Budi Bhakti; Rendi Prasetya (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
The misconception of physics is a difference in understanding concepts known to students with actual concepts. The student's physics misconception profile must be identified for the student to have a correct understanding of the concept—diagnostic tests as a solution to uncover the causes or factors of misunderstanding the physics concept in students. One type of diagnostic test is 4 tier tests. The purpose of this study was to see if the 4th Tier-Magnetic Diagnostic Test (4T-MDT) can help students identify misconceptions. The study was R&D with a 4D model. The 4T-MDT instrument consists of 20 multiple choice questions. Once the 4T-MDT instrument is validated, an average assessment of 84% is obtained, which means it is worth using and implemented to students. The test results showed that as many as 15 items on the 4T-MDT instrument were valid, had high reliability, different good power, and a good difficulty level. As a result, the 4T-MDT instrument may be used to identify the profile of student physics mistakes about magnetic fields.